Electrochemical immunosensor for the detection of colistin in chicken liver - Kumar, Harsh; Valko, Marian; Alomar, Suliman Y; Alwasel, Saleh H; Cruz-Martins, Natália; Kuča, Kamil; Kumar, Dinesh (3 Biotech, 2022)
An innovative amperometric immunosensor has been developed to detect antibiotic colistin from the chicken liver. Colistin is a antibacterial peptide that has been barred for human consumption, but it is being commonly used as a veterinary drug, and as a feed additive for livestock. In the present work, an immunosensor was developed by immobilizing an anti-colistin Ab onto the CNF/AuNPs surface of the screen-printed electrode. The sensor records electrochemical response in the chicken liver spiked with colistin with CV. Additionally, the characterization of electrode surface was done with FE-SEM, FTIR, and EIS at each step of fabrication. The lower LOD was 0.89 μgKg-1, with a R 2 of 0.901 using CV. Further validation of the immunosensor was conducted using commercial chicken liver samples, by comparing the results to those obtained using traditional methods. The fabricated immunosensor showed high specificity towards colistin, which remained stable for 6 months but with a 13% loss in the initial CV current.
Keywords: Specificity; Colistin antibiotic; Chicken liver; Immunosensor; Toxicity